CORRUPTION AS AN OBSTACLE TO THE RULE OF LAW AND ECONOMIC DEVELOPMENT - Slamkov, Gjorgi (International Scientific Journal Vision, 2024)
Within the framework of the paper, the author elaborates on the issue of corruption and its harmful effect in several segments of social life. It is emphasized that corrupt actions are a negation of the value system which is based on modern civilizational understandings. By denying the system of values, corruption creates a parallel system contrary to the normatively defined one, that is, it acts as its counterthesis and through it opposite effects are created, that is, a parallel system that is aimed at circumventing and breaking the established rules and creating a chaotic state. In that direction, the author also presents the relationship between corruption and the rule of law, completely opposite concepts, where corruption is the negation of the rule of law. If the rule of law is in the direction of the correct application of norms by independent institutions with institutional and personal integrity of employees, then corruption is aimed at undermining such integrity and managing institutions in a way that allows abuse of public powers by individuals or groups . The author emphasizes the impact of corruption on economic growth, the level of poverty and the existence of organized crime. All of these relationships have a common point of connection, which is the disruption of the financial system and enabling the enrichment of corrupt persons through the violation of legal norms. The high level of corruption in a country has a strong negative effect on economic development, since state resources are spent in a way that is contrary to what is legally established, through various forms of abuse, mostly in the area of ​​public procurement, through embezzlement, fraud and similar actions. In addition, the author emphasizes that the high degree of corruption does not create competitive conditions, but illegal monopolies are created and maintained as such, and foreign investors avoid such countries for investment because there is legal uncertainty and dysfunctional institutions. Through the analyzing of the relationship between corruption and organized crime, the author emphasizes that countries with weak institutions and a high degree of corruption are particularly vulnerable, and there the groups that deal with organized crime grow stronger. The author points out that the more organized crime groups become financially powerful, the more their efforts to infiltrate politics, that is, institutions, and therefore also in the implementation of legal regulations, will strengthen. This is a particularly dangerous situation and if they succeed in such a goal, then there are serious problems in the functioning of the legal state.